2018
DOI: 10.1016/j.jash.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic kidney disease as a cardiovascular risk factor: lessons from kidney donors

Abstract: Chronic kidney disease (CKD) is a major risk factor for cardiovascular disease but is often associated with other risks such as diabetes and hypertension and can be both a cause and an effect of cardiovascular disease. Although epidemiologic data of an independent association of reduced glomerular filtration rate with cardiovascular risk are strong, causative mechanisms are unclear.Living kidney donors provide a useful model for assessing the “pure” effects of reduced kidney function on the cardiovascular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
14
0
2
Order By: Relevance
“…In contrast to this, long-term studies have suggested malignancy to outrank cardiovascular disease as a leading cause of death in living kidney donors [ 55 ]. A number of studies have gone on to postulate that the role of hypertension is likely an aspect of adaptive physiological change, but accept that there is adequate uncertainty about long-term outcomes which is fostered by the study limitations [ 56 60 ].…”
Section: Complications Of Postdonation Hypertension In Living Kidnmentioning
confidence: 99%
“…In contrast to this, long-term studies have suggested malignancy to outrank cardiovascular disease as a leading cause of death in living kidney donors [ 55 ]. A number of studies have gone on to postulate that the role of hypertension is likely an aspect of adaptive physiological change, but accept that there is adequate uncertainty about long-term outcomes which is fostered by the study limitations [ 56 60 ].…”
Section: Complications Of Postdonation Hypertension In Living Kidnmentioning
confidence: 99%
“…End‐stage renal disease (ESRD) occurs in the last stages of CKD . Although accumulation of fluids, toxins and wastes in the body is the primary dilemma in ESRD, patients are affected by comorbidities such as cardiovascular diseases, mainly as a result of blood lipid disorders, hypertension, oxidative stress and inflammation …”
Section: Introductionmentioning
confidence: 99%
“…Учитывая отсутствие в нашей работе группы сравнения, мы сопоставили частоту традиционных, прежде всего используемых для подсчета SCORE, ФР при БДПК и подагре, другом микрокристаллическом артрите, сходном по механизмам воспаления, а также, возможно, и по некоторым ФР (например, прием мочегонных препаратов [29], наличие ХБП [30]), а также при БДПК и РА, характеризующихся наличием хронического системного воспаления и высоким риском ССЗ [31,32]. И в том и в другом случае речь идет о заболеваниях с высоким риском ССЗ, превышающим популяционный [15,33].…”
Section: Discussionunclassified